Pelaksanaan Workshop Duta Moderasi Beragama Angkatan I pada Mahasiswa IAIN Madura dalam Menguatkan Platform Moderasi Beragama - Masti Yanto; Nailatur Rizqiyah; Waqiatul Masrurah (Indo Publishing, 2025)
The implementation of the Religious Moderation Workshop for IAIN Madura Students is a Transformation of the strengthening of the Religious Moderation Platform in the future. This study uses a Descriptive-qualitative approach with conceptual data collection, namely through critical analysis. The purpose of this study is to strengthen the potential of Religious Moderation values among IAIN Madura students. The findings of this study indicate that the Implementation of Religious Moderation in the process of instilling Tolerance values is a very central role in finding the Pioneers of Religious Moderation Ambassadors and Drivers of Religious Moderation itself. In conclusion, the Religious Moderation Ambassador Workshop can be the first reference in forming and revitalizing the application of Religious Moderation in the community.